Numerical analysis of thermal transportation in nanodiamond and silver-based nanofluid using the Cattaneo–Christov heat flux model - Zuhra, Samina; Sikander, Waseem; Elkotb, Mohamed Abdelghany; Tag-Eldin, E. M.; Khattak, Sana Gul; Yassen, Mansour F. (Frontiers in Energy Research, 2022)
Background and Purpose: Studying the effects of suction and injection on heat transportation in nanofluid for time-dependent boundary layer flow is the key topic in the fluid dynamic. Aerodynamics and the sciences of space both make extensive use of these types of flow. In this research nano-diamond and silver nanoparticles in base fluid water type’s nanofluids flow are taken under the effect of thermal radiation and non-Fourier theory. Methodology: Mathematical system having certain physical variations of the flow model converted to non-dimensional ODEs system via suitable similarity transformation variables. Then the flow model is numerically solved by RK-4 and a shooting technique to describe the dynamics of the nanofluids under varied flow conditions. RK-4 with shooting approach gives a rapid result with high convergence accuracy. Relevant characteristics of physical quantities evaluated by an inclusive numerical scheme are observed for flow pattern, temperature distribution, and nanofluids concentration variations in the presence of suction and injection fluxes. Finding: According to the findings, both ND-H2O and Ag-H2O have outstanding thermal performance characteristics. The Ag-based nanofluid, on the other hand, has a better heat transfer capability. To validate the analysis, a graphical and tabular comparison is offered under specified assumptions. The key finding is that with the injection effect, the heat flow rate is larger than with the suction effect. The unsteadiness parameter causes to drop in the velocity profile, whereas energy distribution rises with this parameter.